Maturation of the gilt's uterus before puberty: response to progesterone at different ages - Groothuis, P.G.; Blair, R.M.; Davis, Duane L. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
We determined the age at which progesterone induced certain responses in the gilt's uterus. The prepubertal maturation permitting each response is being studied currently with the intent of using the information to develop methods to improve litter size in pigs, perhaps by identifying markers for uterine function that could be used before gilts enter the breeding herd.
Keywords: Swine; Gilt; Uterus; Progesterone